Pengembangan Purwarupa Platform Digital Pelaporan Nilai Siswa Sebagai Pendukung Kurikulum Merdeka Berbasis Aplikasi Web di Lingkungan Sekolah Binekas - Septiawan, Reza Rendian; Nasution, Surya Michrandi; Afinda, Angel Metanosa; Ruriawan, Muhammad Faris (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
Sekolah Binekas is a private school in South Bandung that has implemented the Merdeka Curriculum in its learning process. However, monitoring students’ learning achievements is still done manually using traditional records or basic digital spreadsheets, making it difficult for teachers and school management to analyze progress systematically. This community service project aimed to develop a prototype of a web-based digital reporting system to enable real-time tracking of student learning outcomes. The development process involved requirement analysis, user interface design, and system implementation using a user-centered design approach. The system enables efficient data entry, assessment recap, and learning achievement visualization, offering better accuracy and usability than manual methods. Furthermore, it supports school administrative tasks, such as preparing reports for accreditation and evaluating the curriculum. Trial use at Sekolah Binekas indicated that the system simplifies assessment data access for teachers and aids school management in making data-driven decisions. The system offers a practical contribution to a more structured, digital, and locally adaptive monitoring process for Merdeka Curriculum implementation.